Improving Students’ English Vocabulary Mastery Through the Learning Media "Card Games" - Armelia, Nanda; Sudarmarji, Imam; Nuraini, Hery; Forsia, Lastry; Nirmala, Nirna (Jurnal Basicedu, 2024)
This study aims to improve students' mastery of English vocabulary through "card game" learning media. This research was conducted in grade 2 elementary school in Tangerang district by using classroom action research (PTK) approach in 2 cycles. The results showed that the use of card game learning media can improve students' vocabulary mastery. The number of students in this study was 11 students. It was found that there was a significant increase in students' vocabulary mastery from cycle 1 to cycle 2. Thus, it can be concluded that card games are effective in improving students' English vocabulary mastery in grade 2